Periphyton production in a man - made lake - Singh, D N; Sukumaran, P K; Das, A K (Indian Journal of Fisheries, 2011)
In Manchanbele Reservoir the periphytic study exhibited a single peak in July(1060 n/cm2) during first year but two peaks being primary in November &March (1260 & 1250 n/cm2 respectively) and secondary in February & June(940 n/cm2 - each) were recorded in the second year. Lowest population of periphyton was recorded in September during both the years (37 & 73 n/cm2). Bacillariophyceae dominated both the years, being 98.14% in the first and 95.49% in the second year. Rainwater incursion and physico-chemical features of water played a great role in deciding the abundance of periphytic community. Production of periphyton in general was poor due to persisting high turbidity and low nutrients.